Indeks Massa Tubuh (IMT) dan Aktivitas Fisik sebagai Faktor Risiko Kejadian Hipertensi - Khumaeroh, Ana; Fauzia, Wilda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study analyzes the relationship between body mass index and physical activity with hypertension in the Kemayoran Health Center work area. The method used is a cross-sectional design. The study results showed a p-value of 0.020 on the BMI variable and 0.045 on the physical activity variable. In conclusion, a significant relationship exists between body mass index (BMI) and hypertension and between physical activity and hypertension in the Kemayoran Health Center work area. Keywords: Physical Activity, Hypertension, Body Mass Index (BMI)